(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper presents the modeling of a Wind Diesel Hybrid System (WDHS) comprising a Diesel Generator (DG), a Wind Turbine Generator (WTG), the consumer Load, a Ni–Cd Battery based Energy Storage System (BESS) and a Distributed Control System (DCS). All the models of the previously mentioned components are presented and the performance of the WDHS is tested through simulation. Simulation results with graphs for frequency and voltage of the isolated power system, active powers generated/absorbed by the different elements and the battery voltage/current/state of charge are presented for negative load and wind speed steps. The negative load step reduces the load consumed power to a level less than the WTG produced power, so that to balance active powers a negative DG power is needed (DG reverse power). As the DG speed governor cannot control system frequency in a DG reserve power situation, it is shown how the DCS orders the BESS to load artificially the system until the DG power falls in a positive power interval. The negative wind step decreases the WTG produced power, returning the power system to a situation where the needed DG power returns to positive, so that the BESS is not needed to load the system